Pengembangan Smart Tourism berbasis E-Government pada Dinas Kebudayaan dan Pariwisata Provinsi Jambi - Saro, Dewi Novita; Herdiansyah, Izman; Negara, Edi Surya; Sutabri, Tata (Jusikom : Jurnal Sistem Komputer Musirawas, 2024)
All activities, including tourism businesses, can now become more productive and efficient with the rapid development of information, communication, and technology (ICT). The government of a region plays a significant role in managing tourism. In line with Presidential Instruction No. 3 of 2003, which regulates the implementation of electronic government in Indonesia, it mandates the application of e-Government. By utilizing e-Government to be more flexible and user-friendly, the bureaucratic and rigid impression of government services can be eliminated. Additionally, e-Government provides public services that can be accessed anytime, from anywhere.